Argentine Cinema and National Identity 1966-1976 (Volume 16) - Rocha, Carolina (Liverpool University Press, 2018)
Argentine Cinema and National Identity covers the development of Argentine cinema since the late 1950s to the mid-1970s, a period that has been understudied. This essential cultural history delves on the dialect tradition versus modernity that was in place during those years and also comprises an examination of the political economy of film production as well as the different laws, including that implementing censorship that regulated this cultural industry. It also pays particular attention to two historical film genres: the historical film genre per se and the gauchesque, a genre based on outlaw gauchos that was crucial for nation-building in the nineteenth century. This volume investigates the way Argentine cinema positioned itself when facing the competition of glossy American films and resorted to the historical and gauchesque to bridge the stark divisions between the Argentine left and right in the late 1960s.